Challenges, actors and practices of non-formal and informal learning and its validation in Europe - Damesin, Renaud [Verfasser]; Fayolle, Jacky [Verfasser]; Fleury, Nicolas [Verfasser]; Malaquin, Mathieu [Verfasser]; Rode, Nicolas [Verfasser] (My University, 2014)
"For over ten years, the dynamic management of people's vocational pathways and transitions has been attracting the close attention of European social and political players. In this context, non-formal and informal learning (NFIL) practices, as well as the possibility of NFIL recognition and validation, can benefit a wide range of social groups, in particular the most vulnerable, and contribute towards correcting educational inequalities. They can also have a significant impact on the whole system of access to knowledge, skills and competences within companies and on the labour market. This book presents and updates the contents of a project conducted by a team from Groupe ALPHA for the European Trade Union Confederation (ETUC) on NFIL practices and challenges in the EU, including a direct survey of ten Member States." (Publisher, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Informelles Lernen; Non-formales Lernen; Anerkennung; Europa